Optimal tour constructions for multiple mobile robots - Shafie, Amir Akramin (Taylor's University, 2011)
The attempts to use mobile robots in a variety of environments are currently being limited by their navigational capability, thus a set of robots must be configured for one specific environment. The problem of navigating an environment is the fundamental problem in mobile robotic where various methods including exact and heuristic approaches have been proposed to solve the problem. This paper proposed a solution to the navigation problem via the use of multiple robots to explore the environment employing heuristic methods to navigate the environment using a variant of a Traveling Salesman Problem (TSP) known as Multiple Traveling Salesman Problem (M-TSP). © School of Engineering, Taylors University.